Process in contemporary visual art as a paradigm shift in the visual art education: perspective of creativity - Vuk, Sonja; Bosnar, Maja (Creativity Studies, 2021)
The authors discuss contemporary visual art, its creation processes and their implementation in art education in primary and secondary/grammar school. Changing the paradigm of studying from “fine to visual arts” within art education is a process itself. Visual art, which involves a participatory and new media art, is also concerned with processes that establish unique relationships between subjects and their effect on the real life of the participants or audience. It is no longer enough to deal with aesthetic concepts, but it is necessary to use art forms to create everyday life, and deal with ethical concepts. Transferring these processes into education connects students’ creative activities and their everyday life context, so that they can learn how to create social and personal relationships by using images. Experimental research in grammar school affirms the importance of teaching topics as are socially and politically engaged art or artistic activism, mediated by new media. Action research in elementary school affirms proposed style of art education as an acceptable way of transferring the way of thinking from visual art, especially a participatory and new media art, to the process of education as a discovering problems in society and offering solutions represented by visual forms.